PENGEMBANGAN DESAIN PRODUK BERBAHAN BAMBU DENGAN MENGGUNAKAN STRATEGI DESAIN DI NAGARI KUMANIS SIJUNJUNG (STUDI KASUS ; UKM KERAJINAN BAMBU DI NAGARI KUMANIS, KABUPATEN SIJUNJUNG) - Malik, Kendall; Fernando, Ferry; Amalia, Silvi (Jurnal Seni, Desain dan Budaya)
AbstractThe research focused is on bamboo crafts in Nagari Kumanis, Sijunjung Regency, about the use of bamboo material as a potential product using a design strategy. Bamboo production areas in West Sumatra are mostly produced in Sumpur Kudus district in Nagari Tanjung Bonai Aur and Kumanis, Sijunjung Regency. Nagari has a group called Talago Bamboo Crafts. One of the bamboo handicraft centers that has long been developing in West Sumatra is the Tanjung Bonai Aur and Kumanis bamboo crafts. It is known that bamboo crafts in Kumanis nagari are quite unique in terms of technical aspects, but in the aspect of design strategies and market strategies of bamboo products have not been explored properly. So that the economic and production cycle moves in place. Bamboo plantations in West Sumatra belong to communities that are managed independently by the population. Bamboo in the Kumanis nagari community is important by the economic wheel and their economic bamboo efforts as a side job. In fact, Minang residents already have a bamboo garden that is indirectly as a bamboo farmer. This is an opportunity for writers in this design project to provide ideas and design ideas to communities and small industries (homeindustry). In fact, bamboo material has not been specially processed for product design, especially for bamboo product design and Design Strategies. the problem of this research is how to improve, process and utilize bamboo material as one of the development of interior complementary designs and in accordance with market needs and tastes.Keywords : Bamboo, Product Design, Design Strategy, KumanisAbstrak Penelitian yang difokuskan adalah mengenai kerajinan bambu di Nagari Kumanis Kabupaten Sijunjung tentang pemanfaatan material bambu sebagai produk potensial dengan menggunakan strategi desain.  Daerah produksi bambu di Sumatera Barat sebagian besar diproduksi di kabupaten Sumpur Kudus di Nagari Tanjung Bonai Aur dan Kumanis, Kabupaten Sijunjung. Nagari memiliki kelompok yang disebut Kerajinan Talago Bambu. Salah satu pusat kerajinan bambu yang telah lama berkembang di Sumatera Barat adalah kerajinan bambu Tanjung Bonai Aur dan Kumanis. Diketahui bahwa kerajinan bambu di nagari Kumanis cukup unik dalam hal aspek teknis, namun dalam aspek strategi desain dan strategi pasar produk bambu belum dieksplorasi dengan baik. Sehingga siklus ekonomi dan produksi bergerak di tempat. Perkebunan bambu di Sumatera Barat adalah milik masyarakat yang dikelola secara mandiri oleh penduduk. Bambu dalam masyarakat nagari Kumanis adalah penting oleh roda ekonomi dan upaya bambu ekonomi mereka sebagai pekerjaan sampingan. Bahkan, warga Minang telah memiliki kebun bambu yang secara tidak langsung sebagai petani bambu. Ini adalah kesempatan bagi penulis dalam proyek desain ini untuk memberikan ide dan ide desain kepada komunitas dan industri kecil (homeindustry). Padahal, bahan bambu belum diolah secara khusus untuk desain produk, terutama untuk desain produk bambu dan Strategi Desain. permasalahan dari penelitian ini adalah bagaimana meningkatkan, mengolah dan memanfaat material bambu sebagai salah satu perkembangan desain pelengkap interior dan sesuai dengan kebutuhan dan selera pasar.Kata kunci: Bambu, Desain Produk, Strategi Desain, Kumanis